NEW MEDIA AND THE CHANGING LANDSCAPE OF POLITICAL COMMUNICATION - Melyana R Pugu; Nina Triolita; Muhammad Yusuf (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the last decade, the penetration of new media into everyday life, particularly through the use of the internet and social media, has played an important role in shaping contemporary patterns of political communication. This research aims to examine how new media has changed the landscape of political communication and its impact on public participation in the democratic process. Through literature analysis, this study explores various aspects of the changes brought about by new media, including greater accessibility to political information, personalization of political messages, as well as the challenges of echo chambers and polarization that result. The research method used in this study is literature review. The results of this study show that new media have provided new opportunities and challenges in political communication. On the one hand, new media allow politicians to reach out and interact with voters directly and more personally, and promote wider public participation in the political process. On the other hand, phenomena such as echo chambers and online polarization raise concerns about the quality of democratic discussion and the ability of voters to make well- informed decisions. This research emphasizes that while new media provides great opportunities for democracy, there is an urgent need for effective mitigation strategies so that its negative impacts can be minimized.